Polarization maintaining optical fiber and preparation method thereof

By doping the stress region of polarization-maintaining fiber with boron, germanium, and fluorine, and combining it with high-temperature, low-tension fiber drawing technology, the problems of cracking and insufficient birefringence performance of polarization-maintaining fiber under high temperature and high humidity environments have been solved, and the stability and high-performance transmission of optical fiber under extreme environments have been achieved.

CN119270422APending Publication Date: 2025-01-07YANGTZE OPTICAL FIBRE & CABLE CO LTD

Patent Information

Application Number
CN202411680687.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Polarization-maintaining optical fibers are prone to cracking in the stress zone under long-term high temperature and high humidity conditions, and their birefringence performance is insufficient, which affects their application in extreme environments.

Method used

By doping boron, germanium, and/or fluorine in the stress region of polarization-maintaining fiber to control its molar percentage and refractive index difference, and performing melt drawing under high temperature and low tension, a compact boron-oxygen tetrahedral structure is formed, ensuring the structural stability and birefringence performance of the fiber under high temperature and high humidity environments.

Benefits of technology

It significantly reduces the cracking rate of optical fiber stress zone under high temperature and high humidity environment, maintains good birefringence performance, and meets the application requirements in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119270422A_ABST
    Figure CN119270422A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of optical fibers, and particularly discloses a polarization maintaining optical fiber and a preparation method thereof, and the polarization maintaining optical fiber comprises a core layer, at least one stress region and a cladding layer; the core layer is embedded in the center of the cladding, the at least one stress area is embedded in the cladding, and the at least one stress area is uniformly dispersed around the core layer; the stress region is doped with boron, germanium and / or fluorine; at least part of boron exists in the stress region in the form of a boron-oxygen tetrahedron; in the stress region, the molar percentage of B2O3 is greater than the molar percentage of GeO2 and / or F. Through the application, the polarization-maintaining optical fiber with good birefringence performance can be obtained, and the polarization-maintaining optical fiber does not crack in a severe environment for a long time, and can meet the application requirements in the severe environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of optical fiber technology, and more specifically, relates to a polarization-maintaining optical fiber and a preparation method thereof. Background Art

[0002] Polarization-maintaining fiber artificially introduces birefringence to keep the birefringence at each axial position in the fiber unchanged, thereby maintaining the polarization state of the incident light. This feature makes polarization-maintaining fiber play an irreplaceable role in high-speed optical transmission systems, coherent optical communications, and optical fiber sensing.

[0003] In the field of optical device manufacturing, grindable device polarization-maintaining optical fiber is widely used. It is often used to manufacture high-precision, high-performance fiber gyroscopes, fiber sensors, and key components in fiber-optic communication systems. It not only maintains the advantages of traditional polarization-maintaining optical fiber in transmitting linear polarized light, but also has the characteristics of being grindable and can be precisely adjusted in size and shape according to specific application requirements, so as to better meet the design requirements of optical devices and be prepared into various polarization-maintaining connectors. This design, which is easy to plug and unplug and couple, can make polarization-maintaining optical fiber more flexibly adapt to various complex optical device structures and application scenarios.

[0004] Traditional device polarization-maintaining optical fibers need to have a certain degree of grindability, but in long-term high temperature and high humidity environments, due to the thermal expansion coefficient of the material in the stress zone of the polarization-maintaining optical fiber itself, humidity sensitivity, and excessive stress distribution, it is often prone to cracking, thus affecting its performance and life. This problem limits the application of polarization-maintaining optical fibers in extreme environments and affects the normal operation of communication equipment.

[0005] The existing device-type polarization-maintaining optical fibers have the following main problems: (1) The optical fiber has a high grinding cracking rate; (2) The optical fiber has insufficient birefringence performance; (3) The optical fiber stress zone is prone to cracking under long-term high temperature and high humidity conditions; The birefringence performance of polarization-maintaining optical fiber is mainly related to factors such as the stress zone diameter, the doping concentration of the thermal expansion material, the distance between the stress zone and the core layer, and the drawing furnace temperature. The common thermal expansion material in the stress zone is B2O3. If the B2O3 doping concentration is too high in order to increase the birefringence coefficient of the optical fiber, it will lead to greater tensile stress in the slow axis direction of the optical fiber, which will lead to cracking of the stress zone during grinding. At the same time, because higher B2O3 is more likely to chemically react with water molecules under high temperature and high humidity conditions to produce boric acid, it will cause the stress zone of the optical fiber to crack in harsh environments.

[0006] Patent document CN112305664A provides a multi-purpose polarization-maintaining optical fiber. The disclosed technical solution mentions that a core rod is deposited in a tube, and a phosphorus-doped silica inner cladding and a phosphorus-doped silica outer cladding are sequentially prepared on the outside of the core by an external spraying method outside the tube. The above method is relatively cumbersome, and the prepared optical fiber has poor structural stability in the stress zone of the optical fiber under long-term high temperature and high humidity conditions. This is because phosphorus pentoxide is very easy to react chemically with water to generate phosphoric acid, which in turn destroys the structure of the stress zone of the optical fiber and is prone to cracking.

[0007] Patent document CN104591534A provides a method for manufacturing polarization-maintaining optical fiber. The disclosed technical solution mentions that the core rod and the sleeve of the stress zone are prepared by wire cutting, and then the polarization-maintaining preform is prepared by externally nesting the sleeve. During the high-temperature drawing process, the stress zone softens and fills the gap in the gap, thereby preparing the polarization-maintaining optical fiber. The above method is more complicated and requires secondary nesting. Compared with the traditional polarization-maintaining preparation method, the core rod is not first melted and shrunk with the sleeve into a solid rod, and there is a certain gap between the core rod and the sleeve. During the drawing process of the preform, there may be asymmetry of the stress rods on both sides, which squeezes the core rod, and finally causes the core rod to shift, affecting the core package concentricity and birefringence performance of the optical fiber. Summary of the invention

[0008] In view of the defects of the prior art, the purpose of the present application is to provide a polarization-maintaining optical fiber and a preparation method thereof, aiming to solve the problem that the polarization-maintaining optical fiber is prone to cracking in the stress zone under long-term high temperature and high humidity conditions and its birefringence performance cannot be guaranteed.

[0009] To achieve the above objectives, in a first aspect, the present application provides a polarization-maintaining optical fiber, comprising: at least one stress region and a cladding; The core layer is embedded in the center of the cladding layer, the at least one stress zone is embedded in the cladding layer, and the at least one stress zone is evenly dispersed around the core layer; The stress region is doped with boron and germanium and / or fluorine; at least part of the boron in the stress region exists in the form of boron oxygen tetrahedron; the molar percentage of B2O3 in the stress region is greater than the molar percentage of GeO2 and / or F, and the refractive index difference between the stress region and the cladding ranges from -0.0125 to 0.

[0010] It should be noted that, in the stress zone of the polarization-maintaining optical fiber provided by the present application, at least part of the boron exists in the form of boron-oxygen tetrahedrons, which makes the structure of the stress zone more compact, and can greatly reduce the probability of cracking in the stress zone of the optical fiber under a long-term high temperature and high humidity environment; in addition, in the present application, on the basis of conventional polarization-maintaining optical fiber, the doping of at least one element of Ge and F is added. Since the Ge and F elements will not react with water molecules in a high temperature and high humidity environment and the F element can make the borosilicate glass structure more compact, while ensuring that basically no grinding cracking occurs, the problem that the original doped B2O3 is easy to react with water molecules in a high temperature and high humidity environment and thus cause cracking in the stress zone is solved.

[0011] In a possible implementation, when the stress region is doped with boron and germanium, the molar percentage of B2O3 in the stress region is 15%~19%, and the molar percentage of GeO2 in the stress region is 0.1%~2.5%; the refractive index difference between the stress region and the cladding ranges from -0.0125 to 0.

[0012] As a further example, the stress birefringence coefficient of the polarization-maintaining optical fiber is not less than 7.0×10 -4 .

[0013] In a possible implementation, when the stress region is doped with boron and fluorine, the molar percentage of B2O3 in the stress region is 16%~20%, and the molar percentage of F is 0.1%~1%; the refractive index difference between the stress region and the cladding ranges from -0.0125 to -0.0108.

[0014] As a further example, the stress birefringence coefficient of the polarization-maintaining optical fiber is in the range of 4.0×10 -4 ~7.0×10 -4 .

[0015] In a possible implementation, when the stress region is doped with boron, germanium and fluorine, the molar percentage of B2O3 in the stress region is 13%~22%, the molar percentage of GeO2 is 0.1%~3%, and the molar percentage of F is 0.1%~2%; the refractive index difference between the stress region and the cladding ranges from -0.0108 to 0.

[0016] As a further example, the stress birefringence coefficient of the polarization-maintaining optical fiber is not less than 8×10 -4 .

[0017] In a possible implementation, the refractive index difference between the core layer and the cladding layer ranges from 0.0042 to 0.058.

[0018] In a possible implementation, the ratio of the diameter of the stress zone to the diameter of the cladding is in the range of 0.25 to 0.35, and the shortest distance between the outer edge of the stress zone and the outer edge of the core layer is 1 μm to 3 μm.

[0019] It should be noted that the shortest distance between the stress zone and the core layer in the present application is relatively close, and the ratio of the stress zone diameter to the cladding diameter is reasonably designed, so that the polarization-maintaining optical fiber provided in the present application has good birefringence performance.

[0020] In a possible implementation, the grinding cracking rate of the polarization-maintaining optical fiber is 0%, and the cracking rate in a high temperature and high humidity environment for a preset time is lower than a preset value.

[0021] It should be noted that the above-mentioned preset time may be 2000 hours, and the above-mentioned high temperature and high humidity environment may be an environment in which the temperature and humidity are 85° C. and 85% RH respectively.

[0022] In a second aspect, the present application provides a method for preparing a polarization-maintaining optical fiber as described in the first aspect or any possible implementation of the first aspect, comprising the following steps: preparing a core rod, sintering and stretching the core rod and the quartz sleeve to obtain a mother rod; Prepare a bare boron rod; the raw materials of the bare boron rod include: germanium tetrachloride and / or hexafluoroethane, oxygen, silicon tetrachloride and boron trichloride; wherein the ratio of the oxygen flow rate to the sum of the flow rates of other raw materials except oxygen is ≥4; At least one through hole is symmetrically opened in the mother rod to avoid the core rod, and bare boron rods are respectively placed in the at least one through hole to obtain an optical fiber preform; The optical fiber preform is melt-drawn to obtain a polarization-maintaining optical fiber, and the core rod, bare boron rod and quartz sleeve correspond to the core layer, stress area and cladding of the polarization-maintaining optical fiber respectively.

[0023] It should be noted that when depositing a bare boron rod, a mixed gas of silicon tetrachloride, oxygen, boron trichloride, germanium tetrachloride and hexafluoroethane can be introduced into a quartz sleeve to react and generate silicon dioxide doped with boron germanium or boron fluorine or boron germanium fluorine, which is deposited on the sleeve. After that, the outer quartz sleeve is completely polished off to obtain a bare boron rod. The ratio of the oxygen flow rate to the sum of the flow rates of silicon tetrachloride, boron trichloride and germanium tetrachloride needs to be ≥4, so that sufficient oxygen can be combined with the boron element to transform the layered structure of the boron oxygen triangle [BO3] into the mesh structure of the boron oxygen tetrahedron [BO4], which can make the stress area structure more compact and the reliability performance more stable.

[0024] In a possible implementation, the temperature of the melt drawing is greater than 2000° C., and the drawing tension is ≤60 g.

[0025] In a possible implementation, the closest distance between the inner edge of the through hole in the mother rod and the outer edge of the core rod is 0.4 mm to 1.2 mm.

[0026] In a possible implementation, the raw material of the core rod includes at least one or more of the following raw materials: germanium tetrachloride, hexafluoroethane, silicon tetrachloride, erbium chloride, and ytterbium chloride.

[0027] In general, the above technical solutions conceived by the present application have at least the following beneficial effects compared with the prior art: (1) The present application provides a polarization-maintaining optical fiber and a method for preparing the same. On the basis of conventional polarization-maintaining optical fiber, at least one element of Ge and F is doped. Since Ge and F elements will not react with water molecules in a high temperature and high humidity environment and F element can make the borosilicate glass structure more compact, while ensuring that grinding cracking basically does not occur, the problem that the original doped B2O3 easily reacts with water molecules in a high temperature and high humidity environment, thereby causing cracking in the stress zone, is solved.

[0028] (2) The present application provides a polarization-maintaining optical fiber and a method for preparing the same. By controlling the concentration ratio and refractive index range of B, Ge and / or F, the diameter ratio of the stress zone to the cladding, and the closest distance between the outer edge of the stress zone and the outer edge of the core layer, the polarization-maintaining optical fiber is ensured to have a high stress birefringence coefficient in different ranges.

[0029] (3) The present application provides a polarization-maintaining optical fiber and a method for preparing the same. By completely grinding off the quartz sleeve surrounding the boron rod and controlling the edge of the hole to be as close to the core layer as possible, the optical fiber has a larger stress birefringence coefficient. In addition, due to the use of high furnace temperature and low tension drawing, the problem of bubbles being easily trapped at the edge of the stress zone during the preparation of the polarization-maintaining optical fiber is effectively solved. At the same time, the high furnace temperature drawing will also make the temperature difference of the optical fiber larger when it is cooled, and then the squeezing force of the stress zone on the core layer will be greater, resulting in a larger stress birefringence coefficient.

[0030] (4) The present application provides a polarization-maintaining optical fiber and a method for preparing the same. By controlling the ratio of the oxygen flow rate of the deposited boron rod to the sum of the flow rates of silicon tetrachloride, boron trichloride, germanium tetrachloride and / or hexafluoroethane to be ≥4, it is ensured that there is sufficient oxygen to combine with the boron element, so that the layered structure of the boron-oxygen triangle [BO3] in the stress zone of the polarization-maintaining optical fiber is converted into a network structure of the boron-oxygen tetrahedron [BO4]. The latter makes the structure of the polarization-maintaining optical fiber more compact, while ensuring that grinding cracking basically does not occur, so that the structure of the optical fiber stress zone is stable under long-term high temperature and high humidity environment, thereby greatly reducing the cracking rate of the optical fiber stress zone under harsh environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a flow chart of a method for preparing a polarization-maintaining optical fiber provided in an embodiment of the present application; Figure 2 Schematic diagram of the radial structure of a polarization-maintaining optical fiber provided in an embodiment of the present application; Figure 3is a refractive index profile distribution diagram of a polarization-maintaining optical fiber provided in an embodiment of the present application; Figure 4 It is a correlation diagram between the probability of cracking in the stress zone and the wet heat time of a polarization-maintaining optical fiber provided in an embodiment of the present application under the condition that the molar content of B2O3 is 22%; Figure 5 This is the correlation diagram between the stress zone cracking probability and wet heat time of the conventional stress zone pure boron-doped polarization-maintaining optical fiber under the same B2O3 molar content of 22%; Figure 6 This is a correlation diagram between the probability of cracking due to grinding of a polarization-maintaining optical fiber and the molar content of B2O3 in the stress area provided in an embodiment of the present application; Figure 7 This is the correlation diagram between the grinding cracking probability of pure boron-doped polarization-maintaining optical fiber in the conventional stress zone and the molar content of B2O3 in the stress zone; In all drawings, the same reference numerals are used to denote the same elements or structures, wherein: 1 is a core layer; 2 is a cladding layer; 3 is a stress zone; 4 is an inner coating layer; and 5 is an outer coating layer. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application. In the description of the embodiments of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present application can be understood according to specific circumstances. In the description of the embodiments of the present application, it should be noted that the orientations or positional relationships indicated by terms such as "center", "top", "bottom", "inside" and "outside" are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application. In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0033] First, the technical terms involved in the embodiments of the present application are introduced.

[0034] (1) Refractive index profile The refractive index profile refers to the relationship between the refractive index of each layer of the polarization-maintaining optical fiber and its radius.

[0035] (2) Refractive index difference Assume that the refractive index of material layer A is The refractive index of the B material layer is ; The refractive index difference between material layer A and material layer B is for: - .

[0036] Next, the embodiments of the present application are described in conjunction with the drawings in the embodiments of the present application.

[0037] Figure 1 is a flow chart of a method for preparing a polarization-maintaining optical fiber provided in an embodiment of the present application; Figure 1 As shown, the following steps are included: Step S101, preparing a core rod, sintering and stretching the core rod and the quartz sleeve to obtain a mother rod.

[0038] The prepared core rod is inserted into a quartz sleeve and then sintered and stretched.

[0039] Further optionally, the raw material of the core rod includes at least one or more of the following materials: germanium tetrachloride, hexafluoroethane, silicon tetrachloride, erbium chloride, ytterbium chloride, etc.

[0040] It should be noted that the core rod in the present application is the core component of optical fiber transmission. When the core rod is doped with materials such as erbium chloride or ytterbium chloride, it can be prepared into an active polarization-maintaining optical fiber. The improvements of the polarization-maintaining optical fiber in the present application can be extended to active polarization-maintaining optical fiber. The improvements of the embodiments of the present application do not focus on the specific material system of the core rod. Those skilled in the art can choose according to their needs. The core purpose of the improvements provided by the embodiments of the present application is to ensure the birefringence performance of the optical fiber while improving its structural stability in high temperature and high humidity environments. The following embodiments will no longer specifically describe the specific material system of the core rod.

[0041] Step S102, preparing a bare boron rod; the raw materials of the bare boron rod include: germanium tetrachloride and / or hexafluoroethane, oxygen, silicon tetrachloride and boron trichloride; wherein the ratio of the oxygen flow rate to the sum of the flow rates of other raw materials except oxygen is ≥4.

[0042] Specifically, the preparation steps of the bare boron rod may be: preparing the boron rod in a quartz sleeve, and then completely grinding off the quartz sleeve to obtain the bare boron rod.

[0043] It should be noted that when preparing the bare boron rod, a high oxygen-boron-silicon ratio is used to ensure that there is enough oxygen to combine with the boron element, so that the layered structure of the boron-oxygen triangle [BO3] is transformed into the network structure of the boron-oxygen tetrahedron [BO4]. Therefore, most of the boron in the boron rod is in the form of boron-oxygen tetrahedron [BO ] The existence of the boron rod makes the structure more compact and the reliability performance more stable, which can greatly improve the structural stability of the stress zone of the polarization-maintaining optical fiber in a long-term high temperature and high humidity environment.

[0044] Preferably, the above flow ratio may be ≥6 to form more boron-oxygen tetrahedrons [B ], further ensuring the structural stability of the stress zone of the polarization-maintaining optical fiber in a long-term high temperature and high humidity environment, and greatly reducing the cracking rate of the optical fiber stress zone in harsh environments.

[0045] Step S103, at least one through hole is opened in the mother rod avoiding the core rod, and bare boron rods are respectively placed in the at least one through hole to obtain an optical fiber preform.

[0046] Step S104, melt-drawing the optical fiber preform to obtain a polarization-maintaining optical fiber, wherein the core rod, the bare boron rod and the quartz sleeve correspond to the core layer, the stress region and the cladding of the polarization-maintaining optical fiber respectively.

[0047] In one example, a panda-type polarization-maintaining fiber is used as an example to illustrate that the structure of the prepared polarization-maintaining fiber is as follows: Figure 2 See Figure 2 The polarization-maintaining optical fiber comprises: a core layer 1, a cladding layer 2, a stress region 3, an inner coating layer 4, and an outer coating layer 5. It can be understood that when the optical fiber preform is melt-drawn to obtain the polarization-maintaining optical fiber, the core rod after drawing is Figure 1 The core layer 1 in the drawing is the bare boron rod 3. Figure 1 The stress zone 3 in the drawing is the quartz sleeve Figure 1 The cladding 2 in.

[0048] It should be noted that the embodiment of the present application is illustrated by taking two stress zones as an example. The innovative means such as the material system, structural parameters of the stress zone, and the structural parameter design between the stress zone and the core layer can be applied to the polarization-maintaining optical fiber scheme with one stress zone or more than two stress zones (multi-core polarization-maintaining optical fiber). The shape of the stress zone is not limited to a cylindrical shape, but can also be other shapes. Those skilled in the art can adjust it according to actual needs, and the embodiment of the present application does not further limit this.

[0049] Figure 2 In the figure, D1 represents the diameter of the core layer 1, D2 represents the diameter of the cladding layer 2, D3 represents the diameter of the stress zone 3, D4 represents the diameter of the inner coating, D5 represents the diameter of the outer coating, and d represents the distance between the stress zone 3 and the core layer 1, which refers to the distance between the outer side of the stress zone 3 close to the core layer 1 and the outer side of the core layer 1.

[0050] Among them, in combination with the description of the above-mentioned preparation method, the stress zone of the polarization-maintaining optical fiber provided in the embodiment of the present application is doped with boron B, and doped with at least one of germanium Ge and fluorine F; the main function of the B element is to have a high thermal expansion coefficient, but too much B element may bring excessive stress, which is easy to cause grinding cracking, and the higher B2O3 is more likely to react chemically with water molecules under high temperature and high humidity conditions to produce boric acid, which will cause the optical fiber to crack in the stress zone under harsh environments. Since the Ge element also has a large thermal expansion coefficient and GeO2 is not easy to react chemically with water, this problem can be solved by co-doping B and Ge. In addition, since the F element has a negative thermal expansion coefficient, it has a negative effect on the stress birefringence coefficient of the optical fiber, but the F element is not easy to react chemically with water, and since the F ion radius is small and the bonding force with the Si ion is stronger, the borosilicate glass can be made more stable chemically, so the problem of cracking in the stress zone of the optical fiber under harsh environments can also be solved by co-doping B and F, or B, Ge and F.

[0051] Specifically, the difference in the molar percentage of B2O3, GeO2 and / or F in the stress zone of the polarization-maintaining optical fiber is mainly to take into account the different birefringence coefficient requirements, because excessive B2O3 and GeO2 will cause the slow-axis tensile stress of the optical fiber to be too large, which is easy to crack during optical fiber grinding, and even the stress zone is prone to cracking in a long-term high temperature and high humidity environment; similarly, excessive F doping will reduce the stress birefringence coefficient of the optical fiber.

[0052] It can be understood that when two through holes are opened in the mother rod avoiding the core rod, the distance between the inner edge of the through hole close to the core rod and the outer edge of the core rod close to the through hole (at this time, the core rod and the quartz sleeve have been sintered and stretched to obtain the above-mentioned mother rod) is 0.4mm~1.2mm, so as to ensure that the stress zone is closer to the core layer, for example, 1μm~3μm, so that the optical fiber has high birefringence performance.

[0053] Optionally, the ratio range D3 / D2 of the stress zone diameter D3 to the cladding diameter D2 is 0.25~0.35; further, the above ratio range is preferably 0.3~0.35.

[0054] It should be noted that the setting of the distance between the stress zone and the core layer, as well as the ratio of the stress zone diameter to the cladding diameter, can make the stress of the polarization-maintaining optical fiber greater. At the same time, combined with the configuration of the molar ratio of each material in the stress zone, the polarization-maintaining optical fiber can have a greater stress birefringence coefficient. For example, the stress birefringence coefficient is greater than 4.0×10 -4 , so that the polarization-maintaining optical fiber prepared from the above raw materials has good birefringence performance.

[0055] Figure 3 : is a refractive index profile distribution diagram of a polarization-maintaining optical fiber provided in an embodiment of the present application. Figure 3 As shown, assuming that the refractive index of the stress zone is n1 and the refractive index of the cladding (pure silicon dioxide) is n0, then the refractive index difference between the stress zone and the cladding is n1-n0.

[0056] As an example, the refractive index difference between the core layer 1 and the cladding layer 2 ranges from 0.0042 to 0.058.

[0057] It should be noted that the core layer 1 and the cladding layer 2 need to have a certain refractive index difference to form a waveguide structure to ensure the transmission performance of the polarization-maintaining optical fiber.

[0058] Further preferably, when the raw materials of the bare boron rod include germanium tetrachloride, oxygen, silicon tetrachloride and boron trichloride, the molar percentage of B2O3 in the stress zone of the polarization-maintaining optical fiber is 15% to 19%, and the molar percentage of GeO2 is 0.1% to 2.5%; the refractive index difference between the stress zone 3 and the cladding 2 is in the range of -0.0125 to 0; it is found through research that the stress birefringence coefficient of the polarization-maintaining optical fiber is not less than 7.0×10 -4 .

[0059] It is understood by those skilled in the art that when preparing the bare boron rod, the ratio of each raw material should be adjusted so that the molar percentage of B2O3 in the final stress region is 15% to 19%, and the molar percentage of GeO2 is 0.1% to 2.5%. Within the above molar ratio range, the refractive index difference between the stress region 3 and the cladding 2 ranges from -0.0125 to 0. At this time, the birefringence coefficient of the polarization-maintaining optical fiber is not less than 7.0×10 -4 .

[0060] It can be seen that the stress zone of the above B and Ge material system, under the control of the above high oxygen borosilicate ratio, can prepare a polarization-maintaining optical fiber with a corresponding molar ratio. While having good birefringence performance, it is structurally stable under long-term high temperature and high humidity environments and has good application prospects and advantages.

[0061] Further preferably, when the raw materials of the bare boron rod include hexafluoroethane, oxygen, silicon tetrachloride and boron trichloride, the molar percentage of B2O3 in the stress zone of the polarization-maintaining optical fiber is 16%~20%, and the molar percentage of F is 0.1%~1%; the refractive index difference between the stress zone 3 and the cladding 2 ranges from -0.0125 to -0.0108; it is found that the stress birefringence coefficient of the polarization-maintaining optical fiber at this time ranges from 4.0×10 -4 ~7.0×10 -4 .

[0062] As above, when preparing the bare boron rod, the technicians in this field should adjust the ratio of each raw material so that the molar percentage of B2O3 in the final stress zone is 16%~20%, and the molar percentage of F is 0.1%~1%. Within the above molar ratio range, the refractive index difference between the stress zone 3 and the cladding 2 ranges from -0.0125 to -0.0108. At this time, the stress birefringence coefficient of the polarization-maintaining optical fiber is 4.0×10 -4 ~7.0×10 -4 .

[0063] It can be seen that the stress zone of the above-mentioned B and F material systems, under the control of the above-mentioned high-oxygen borosilicate ratio, can prepare a polarization-maintaining optical fiber with a corresponding molar ratio. While maintaining relatively good birefringence performance, it is structurally stable under long-term high temperature and high humidity environments, and also has good application prospects and advantages.

[0064] Further preferably, when the raw materials of the bare boron rod include: germanium tetrachloride, hexafluoroethane, oxygen, silicon tetrachloride and boron trichloride, the molar percentage of B2O3 in the stress zone of the polarization-maintaining optical fiber is 13%~22%, the molar percentage of GeO2 is 0.1%~3%, and the molar percentage of F is 0.1%~2%; the refractive index difference between the stress zone 3 and the cladding 2 ranges from -0.0108 to 0; it has been found that the stress birefringence coefficient of the polarization-maintaining optical fiber is not less than 8×10 -4 .

[0065] As above, when preparing the bare boron rod, the technicians in this field should adjust the ratio of each raw material so that the molar percentage of B2O3 in the final stress zone is 13%~22%, the molar percentage of GeO2 is 0.1%~3%, and the molar percentage of F is 0.1%~2%. Within the above molar ratio range, the refractive index difference between the stress zone 3 and the cladding 2 ranges from -0.0108 to 0. At this time, the stress birefringence coefficient of the polarization-maintaining optical fiber is not less than 8×10 -4 .

[0066] It can be seen that the stress zone of the above-mentioned B, Ge and F material system, under the control of the above-mentioned high oxygen borosilicate ratio, can prepare a polarization-maintaining optical fiber with a corresponding molar ratio. While maintaining good birefringence performance, it is structurally stable under long-term high temperature and high humidity environments, and also has good application prospects and advantages.

[0067] In summary, it can be understood that conventional stress rod grinding will retain some pure silicon to wrap the boron area. This application directly grinds off the pure silicon part outside the boron rod, and then controls the distance between the inner edge of the through hole in the mother rod (the hole for inserting the stress rod (i.e., bare boron rod)) and the outer edge of the core rod to 0.4mm~1.2mm, thereby ensuring that the stress area is closer to the core layer, for example, 1μm~3μm, so that the optical fiber has high birefringence performance. However, for bare boron rods and when they are particularly close to the core layer, it is easy to produce bubbles during the drawing process, affecting the uniformity and consistency of the optical fiber, and cannot guarantee high birefringence performance. Therefore, it is necessary to use high furnace temperature and low tension conditions during the drawing process. The temperature of the drawing furnace needs to be higher than the preset temperature, such as higher than 2000°C, and the drawing tension needs to be less than or equal to the preset force, such as ≤60g; this can ensure that the temperature of the stress zone is high enough. If bubbles are generated during the drawing process, they will float up in the preform rod and will not be drawn into the optical fiber. At the same time, the high furnace temperature drawing will also make the temperature difference of the optical fiber larger when it cools, and then the stress zone will have a greater squeezing force on the core layer, resulting in a larger stress birefringence coefficient.

[0068] In order to better illustrate the performance characteristics of the polarization-maintaining optical fiber provided in the embodiments of the present application, a comparative analysis is further performed through the following specific embodiments, and the relevant parameters of each embodiment are shown in Table 1. Table 1

[0069] Figure 4 This is a correlation diagram between the probability of stress zone cracking and wet heat time of a polarization-maintaining optical fiber provided in Example 6 of the present application under the conditions of a B2O3 molar content of 22%, a GeO2 molar content of 1%, and a F molar content of 2%; Figure 5 This is the correlation diagram between the stress zone cracking probability and the wet heat time of the conventional stress zone pure boron-doped polarization-maintaining optical fiber under the same B2O3 molar content of 22%. Figure 4 and Figure 5 By comparison, it can be seen that when the molar percentage of B2O3 in the conventional stress zone pure boron-doped polarization-maintaining fiber is 22%, the stress zone of the fiber is 100% cracked in a high temperature and high humidity environment for 1400 hours; while in this embodiment, by adding 1% molar percentage of GeO2 and 2% molar percentage of F to the B2O3 molar percentage at 22%, the probability of stress zone cracking in 2000 hours is only 1.4%, and at this time the fiber has high birefringence performance, and its coefficient is 8.6×10 -4It can be seen that the polarization-maintaining optical fiber prepared by the material system and the corresponding preparation method provided in the present application has high birefringence performance and can have very good structural stability in a long-term high temperature and high humidity environment, and has better performance.

[0070] Figure 6 It is a correlation diagram between the probability of cracking due to grinding of polarization-maintaining optical fiber and the molar content of B2O3 in the stress region of the boron-germanium-fluorine (B, Ge and F) system provided in an embodiment of the present application; Figure 7 It is a correlation diagram between the grinding cracking probability of pure boron-doped polarization-maintaining optical fiber in the conventional stress zone and the molar content of B2O3 in the stress zone; Figure 6 and Figure 7 In contrast, when the molar percentage of B2O3 in the conventional stress zone pure boron-doped polarization-maintaining optical fiber is 19%, the grinding cracking rate will reach 4%, while the molar percentage of B2O3 in the polarization-maintaining optical fiber prepared by this application is 22%, and even when it is 25%, the grinding cracking rate is still 0%; it can be seen that the polarization-maintaining optical fiber designed in this application, through the design of the stress zone material system, the distance between the outer edge of the stress zone and the outer edge of the core layer, and the diameter ratio of the stress zone to the core layer, can increase a certain amount of boron doping to improve the birefringence performance of the polarization-maintaining optical fiber while ensuring that the optical fiber grinding cracking rate is basically 0, and the probability of cracking in the stress zone under a long-term high temperature and high humidity environment is also very low; therefore, the polarization-maintaining optical fiber provided by this application not only ensures that its optical fiber end face is not cracked after grinding, but also ensures that the stress zone of the polished optical fiber (optical fiber connector) or the stress zone of the optical fiber that has not been polished has a very low cracking rate under a long-term high temperature and high humidity environment, so the application scheme has a great advantage over the prior art.

[0071] In summary, the end face grinding cracking rate of the polarization-maintaining optical fiber provided by this application is 0%, and the cracking rate of the optical fiber stress zone in a long-term high temperature and high humidity environment is very low. After research, it is found that the cracking rate of the stress zone in a 2000h high temperature and high humidity environment is ≤2%. It can be seen that the polarization-maintaining optical fiber provided by this application, on the basis of the current polarization-maintaining optical fiber technical solution, improves the optical fiber birefringence performance, ensures that it is basically not cracked during grinding, and at the same time, the chemical structure of the optical fiber stress zone is more stable. The stress zone does not crack under long-term high temperature and high humidity conditions, and can meet the demand for polarization-maintaining optical fiber in harsh environments, and has broad application prospects.

[0072] It should be understood that expressions such as "including" and "may include" that may be used in the present application indicate the existence of the disclosed functions, operations, or constituent elements, and do not limit one or more additional functions, operations, and constituent elements. In the present application, terms such as "including" and / or "having" may be interpreted as indicating specific characteristics, numbers, operations, constituent elements, components, or combinations thereof, but may not be interpreted as excluding the existence or possibility of adding one or more other characteristics, numbers, operations, constituent elements, components, or combinations thereof.

[0073] In addition, in the present application, the expression "and / or" includes any and all combinations of the associated listed words. For example, the expression "A and / or B" may include A, may include B, or may include both A and B.

[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A polarization-maintaining optical fiber, characterized in that: include: a core layer, at least one stress zone, and a cladding layer; The core layer is embedded in the center of the cladding layer, the at least one stress zone is embedded in the cladding layer, and the at least one stress zone is evenly dispersed around the core layer; The stress region is doped with boron, germanium and / or fluorine; at least part of the boron in the stress region exists in the form of boron-oxygen tetrahedrons; the molar percentage of B2O3 in the stress region is greater than the molar percentage of GeO2 and / or F.

2. The polarization-maintaining optical fiber according to claim 1, characterized in that: When the stress region is doped with boron and germanium, the molar percentage of B2O3 in the stress region is 15%~19%, and the molar percentage of GeO2 in the stress region is 0.1%~2.5%; the refractive index difference between the stress region and the cladding ranges from -0.0125 to 0.

3. The polarization-maintaining optical fiber according to claim 1, characterized in that: When the stress region is doped with boron and fluorine, the molar percentage of B2O3 in the stress region is 16%~20%, and the molar percentage of F is 0.1%~1%; the refractive index difference between the stress region and the cladding ranges from -0.0125 to -0.0108.

4. The polarization-maintaining optical fiber according to claim 1, characterized in that: When the stress zone is doped with boron, germanium and fluorine, the molar percentage of B2O3 in the stress zone is 13%~22%, the molar percentage of GeO2 is 0.1%~3%, and the molar percentage of F is 0.1%~2%; the refractive index difference between the stress zone and the cladding ranges from -0.0108 to 0.

5. The polarization-maintaining optical fiber according to claim 1, characterized in that: The refractive index difference between the core layer and the cladding layer ranges from 0.0042 to 0.

058.

6. The polarization-maintaining optical fiber according to claim 1, characterized in that: The ratio of the diameter of the stress zone to the diameter of the cladding is in the range of 0.25 to 0.35, and the closest distance between the outer edge of the stress zone and the outer edge of the core layer is 1 μm to 3 μm.

7. A method for preparing the polarization-maintaining optical fiber according to any one of claims 1 to 6, characterized in that: The following steps are involved: preparing a core rod, sintering and stretching the core rod and the quartz sleeve to obtain a mother rod; Prepare a bare boron rod; the raw materials of the bare boron rod include: germanium tetrachloride and / or hexafluoroethane, oxygen, silicon tetrachloride and boron trichloride; wherein the ratio of the oxygen flow rate to the sum of the flow rates of other raw materials except oxygen is ≥4; At least one through hole is symmetrically opened in the mother rod to avoid the core rod, and bare boron rods are respectively placed in the at least one through hole to obtain an optical fiber preform; The optical fiber preform is melt-drawn to obtain a polarization-maintaining optical fiber, and the core rod, bare boron rod and quartz sleeve correspond to the core layer, stress area and cladding of the polarization-maintaining optical fiber respectively.

8. The preparation method according to claim 7, characterized in that: The temperature of the melt drawing is greater than 2000° C., and the drawing tension is ≤60g.

9. The preparation method according to claim 7, characterized in that: The closest distance between the inner edge of the through hole in the mother rod and the outer edge of the core rod is 0.4 mm to 1.2 mm.

10. The preparation method according to claim 7, characterized in that: The raw material of the core rod includes at least one or more of the following raw materials: germanium tetrachloride, hexafluoroethane, silicon tetrachloride, erbium chloride and ytterbium chloride.

Citation Information

Patent Citations

  • Manufacturing method of polarization maintaining optical fiber

    CN104591534A

  • Multipurpose polarization maintaining optical fiber and preparation method thereof

    CN112305664A

Cited By

  • Flow casting preparation process of polarization maintaining optical fiber

    CN121651667A